Proportionality of Willingness to Pay to Small Risk Changes The Impact of Attitudinal Factors in Scope Tests - Andrea M. Leiter; Gerald J. Pruckner (Fondazione Eni Enrico Mattei (FEEM), 2006)
Sensitivity (proportionality) of willingness to pay to (small) risk changes is often used as a criterion to test for valid measures of economic preferences. In a contingent valuation (CV) study conducted in Austria in February 2005 1,005 respondents were asked their willingness to pay (WTP) for preventing an increase in risk by 1/42,500 and 3/42,500, respectively. WTP for the higher risk variation is significantly higher than WTP for the lower risk change. We find evidence that those respondents who have personal experience with avalanches combine the information about future risk increase, provided in the survey, with the observed number of mortal avalanche accidents in the past. The proportionality of WTP holds if such prior experiences are taken into account and the influence of attitudinal factors in scope tests are controlled for.
Keywords: D81; J17; Q54; 330; Contingent Valuation; Willingness to Pay; Scope Test; Sensitivity of WTP; Willingness to pay; Risiko; Österreich; Wert des Lebens